A Quantitative Analysis of the Distribution of CRH Neurons in Whole Mouse Brain - Peng, Jie; Long, Ben; Yuan, Jing; Peng, Xue; Ni, Hong; Li, Xiangning; Gong, Hui; Luo, Qingming; Li, Anan (Frontiers in Neuroanatomy, 2017)
Corticotropin-releasing hormone (CRH), with widespread expression in the brain, plays a key role in modulating a series of behaviors, including anxiety, arousal, motor function, learning and memory. Previous studies have focused on some brain regions with densely distributed CRH neurons such as paraventricular hypothalamic nucleus (PVH) and bed nuclei of the stria terminalis (BST) and revealed some basic structural and functional knowledge of CRH neurons. However, there is no systematic analysis of brain-wide distribution of CRH neurons. Here, we performed a comprehensive study of CRH neurons in CRH-IRES-Cre;Ai3 mice via automatic imaging and stereoscopic cell counting in a whole mouse brain. We acquired four datasets of the CRH distributions with co-localized cytoarchitecture at a voxel resolution of 0.32 μm × 0.32 μm × 2 μm using brain-wide positioning system (BPS). Next, we precisely located and counted the EYFP-labeled neurons in different regions according to propidium iodide counterstained anatomical reference using Neuronal Global Position System. In particular, dense EYFP expression was found in piriform area, BST, central amygdalar nucleus, PVH, Barrington’s nucleus, and inferior olivary complex. Considerable CRH neurons were also found in main olfactory bulb, medial preoptic nucleus, pontine gray, tegmental reticular nucleus, external cuneate nucleus, and midline thalamus. We reconstructed and compared the soma morphology of CRH neurons in 11 brain regions. The results demonstrated that CRH neurons had regional diversities of both cell distribution and soma morphology. This anatomical knowledge enhances the current understanding of the functions of CRH neurons. These results also demonstrated the ability of our platform to accurately orient, reconstruct and count neuronal somas in three-dimension for type-specific neurons in the whole brain, making it feasible to answer the fundamental neuroscience question of exact numbers of various neurons in the whole brain.